Peningkatan Prestasi Belajar IPA tentang Cara Menghasilkan Energi Listrik melalui Pendekatan Kontekstual pada Siswa Kelas VI SDN 008 Nongsa Batam - Marsiyam Marsiyam (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2021)
The purpose of this classroom action research is to improve science learning achievement through a Contextual Approach to class VI students of SDN 008 Nongsa District, Batam City, for the 2019/2020 academic year. The form of this research is classroom action research consisting of two cycles, each cycle consists of four stages, namely planning, implementation, observation and reflection. The subject of the research is the sixth grade student of SDN 008 Nongsa. In data collection, the method used as the main method is observation and test. Based on the results of research on the application of a contextual approach to class VI of SDN 008 Nongsa, with a total of 37 students experiencing an increase in learning outcomes. and in the second cycle it rose to 84.59. The same thing happened to the increase in the number of students who reached the minimum completion limit (>75), namely before the action 12 students (32.43%), who completed the first cycle as many as 24 students (64.86%) and in the second cycle increased to 31 students (83.78%). Thus, it can be concluded that the use of a contextual approach is proven to improve science learning achievement in Grade VI students of SDN 008 Nongsa for the 2019/2020 academic year.